Demographic Data Analysis And Educational System Planning For Primary Education Delivery In Abia State, Nigeria. - Obasi, Kenneth K. (Advances in Social Sciences Research Journal, 2019)
The determination of the level of demographic analysis and educational system planning in the provision of primary education in Abia State, Nigeria was the thrust of this study. The study adopted the descriptive survey design. All the senior staff of the Ministry of Education and the Universal Basic Education Board constituted the population and the respondents. They were 59 in number. The instrument for the generation of data were questionnaire and structured interview. The title of the questionnaire was Demographic Data Analysis and Education System Planning for the provision of Primary Education Questionnaire (DDAESPPPEQ). The items of the instrument were structured based on the four point modified Likert response mode. The data were analyzed with Mean, standard deviation and t-test of difference. The findings of the study include the following: inadequate policy provisions and administrative strategies to ensure effective demographic data collection, analysis and utilization, poor synergistic relationship between the Ministry of Education, UBE Board and the agencies responsible for the generation of demographic data and poor funding. The study therefore recommended among other things that there should be comprehensive policy provision to ensure effective demographic data collection, analysis and utilization, more robust administrative strategies should be adopted for data collection, analysis and utilization and a more comprehensive synergy between the Ministry of Education, UBE Board and demographic data agencies.